2014
DOI: 10.1111/j.1521-0391.2014.12119.x
|View full text |Cite
|
Sign up to set email alerts
|

Problematic alcohol use and sexual assault among male college students: The moderating and mediating roles of alcohol outcome expectancies

Abstract: Background and Objectives Extant research shows a strong relationship between alcohol use problems and sexual aggression. However, less is known about the effect of intermediary factors (eg, alcohol expectations) that may increase the likelihood of and/or explain sexual aggression during alcohol‐related incidents. The present study examined alcohol outcome expectancies' (OE) mediating and/or moderating influence on the relationship between problematic alcohol use severity and sexual aggression among male colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 29 publications
(55 reference statements)
0
14
0
1
Order By: Relevance
“…There may also be an expectancy effect (Collins & Messerschmidt, 1993 ), whereby if a person believes that they will behave in a certain way when they drink alcohol, then they will behave in that way. It has been found that men expect to feel more aggressive and sexually aroused after drinking alcohol (Tuliao & McChargue, 2014 ). This is linked to the deviance disavowal theory (Miller, Maguin, & Downs, 1997 ), which suggests that some people use alcohol as an excuse for premeditated behaviors and then blame those behaviors on alcohol.…”
Section: Discussionmentioning
confidence: 99%
“…There may also be an expectancy effect (Collins & Messerschmidt, 1993 ), whereby if a person believes that they will behave in a certain way when they drink alcohol, then they will behave in that way. It has been found that men expect to feel more aggressive and sexually aroused after drinking alcohol (Tuliao & McChargue, 2014 ). This is linked to the deviance disavowal theory (Miller, Maguin, & Downs, 1997 ), which suggests that some people use alcohol as an excuse for premeditated behaviors and then blame those behaviors on alcohol.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with nonperpetrators, perpetrators drink more heavily (Koss & Gaines, 1993;Locke & Mahalik, 2005;Tuliao & McChargue, 2014) and more frequently within dating and sexual situations (Abbey et al, 2001;Schwartz et al, 2001). Although the positive association between drinking and sexual assault is consistent with a pharmacological effect, heavy drinking men also possess characteristics associated with sexual assault perpetration (e.g., impulsivity, delinquency; Abbey et al, 2006;Thompson et al, 2011).…”
Section: Effects Of Alcohol On Sexual Assault Perpetrationmentioning
confidence: 97%
“…Numerous studies have demonstrated that sexually aggressive men differ from nonsexually aggressive men on many alcohol-related behaviors and beliefs. Sexual assault perpetrators have stronger sexuality-related alcohol expectancies than do nonperpetrators (Abbey, McAuslan, Zawacki, Clinton, & Buck, 2001;Tuliao & McChargue, 2014;Wilson, Calhoun, & McNair, 2002). Sexual assault perpetrators also consume more alcohol, overall and in sexual situations; engage in more heavy episodic drinking; and have more alcohol-related problems (for reviews see Abbey, 2002;Abbey et al, 2014;Testa, 2002).…”
Section: Alcohol As a Risk Factor For Sexual Assault Perpetrationmentioning
confidence: 99%